STUDI PERBANDINGAN PEMBELAJARAN NUMBERED HEADS TOGETHER DENGAN PEMBELAJARAN TWO STAY TWO STRAY - Putri Yulianti; Raden Gunawan Sudarmanto; Yon Rizal (FKIP Unila, 2013)
The aimed of this research was to know wheather there is a difference on result of learning economy between those thaught using cooperative learnig model type NHT and type TSTS and to know which type is more effective between cooperative learning model type NHT and TSTS in economy subject. The experiment method of this research was Quasi Experiment. The design of this research was non-equivalent control group design. The population of this research was the first grade of SMA Negeri 3 Bandar Lampung year 2012/2013 which consisted of seven classes and 266 students. By using cluster random sampling, class x1 and x2 were chosen as the samples. Data collecting technique of this research were observation, documentation and tests. Hypothesis testing was analyzed by using Independent Samples Test. The result shows that (1) there are differences between those taught economy subject by using cooperativelearning type NHT and TSTS, (2) The using of cooperative learning type NHT is more effective than cooperative learning type TSTS in economy subject.Keywords: NHT, TSTS, RS.